Challenges to rational prescribing and use of essential medicines in India - Sekhri, Kavita (International Journal of Basic & Clinical Pharmacology, 2017)
I have read the Editorial entitled ‘Challenges to rational prescribing and use of essential medicines in India’ which was published in your journal with great interest. This has prompted me to address certain issues related to rational prescription of iron supplements in pregnancy.